Ring trial 2016 for Bluetongue virus detection by real‐time RT‐PCR in France - Sailleau, Corinne (Vet Med Sci, 2017)
Since the unexpected emergence of BTV‐8 in Northern Europe and the incursion of BTV‐8 and 1 in France in 2006–2007, molecular diagnosis has considerably evolved. Several real‐time RT‐PCR (rtRT‐PCR) methods have been developed and published, and are currently being used in many countries across Europe for BTV detection and typing. In France, the national reference laboratory (NRL) for orbiviruses develops and validates ‘ready‐to‐use’ kits with private companies for viral RNA detection. The regional laboratories network that was set up to deal with a heavy demand for analyses has used these available kits. From 2007, ring tests were organized to monitor the performance of the French laboratories. This study presents the results of 63 regional laboratories in the ring trial organized in 2016. Blood samples were sent to the laboratories. Participants were asked to use the rtRT‐PCR methods in place in their laboratory, for detection of all BTV serotypes and specifically BTV‐8. The French regional laboratories are able to detect and genotype BTV in affected animals. Despite the use of several methods (i.e. RNA extraction and different commercial rtRT‐PCRs), the network is homogeneous. The ring trial demonstrated that the French regional veterinary laboratories have reliable and robust BTV diagnostic tools for BTV genome detection.